2023
DOI: 10.3389/fimmu.2023.1099079
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the humoral response after three doses of COVID-19 vaccination in kidney transplant recipients

Abstract: IntroductionKidney transplant recipients showed a weak humoral response to the mRNA COVID-19 vaccine despite receiving three cumulative doses of the vaccine. New approaches are still needed to raise protective immunity conferred by the vaccine administration within this group of high-risk patients. MethodsTo analyze the humoral response and identify any predictive factors within these patients, we designed a prospective monocentric longitudinal study of Kidney transplant recipients (KTR) who received three dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Reported research has been focused on the effect of repeated boosting with monovalent mRNA- or viral vector–based vaccine doses. 31-34 Al Jurdi et al 35 found a significant increase in IgG levels against the RBD of BA.2.12.1 and BA.4/BA.5 subvariants (but not for B.1.1.529 or the ancestral strain) after a fourth monovalent vaccine dose among KT recipients. Additionally, both the neutralizing activity and the proportion of patients with neutralizing responses >30% against BA.4/BA.5 also increased with the booster.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported research has been focused on the effect of repeated boosting with monovalent mRNA- or viral vector–based vaccine doses. 31-34 Al Jurdi et al 35 found a significant increase in IgG levels against the RBD of BA.2.12.1 and BA.4/BA.5 subvariants (but not for B.1.1.529 or the ancestral strain) after a fourth monovalent vaccine dose among KT recipients. Additionally, both the neutralizing activity and the proportion of patients with neutralizing responses >30% against BA.4/BA.5 also increased with the booster.…”
Section: Discussionmentioning
confidence: 99%
“…29 In contrast, a number of studies have shown that a fourth dose of the bivalent vaccine induces higher neutralizing responses against BA.2- and BA.5-derived sublineages (including the BQ.1.1 and XBB.1 subvariants). 17,18 In a phase III trial, the BA.1-adapted BNT162b2 vaccine induced higher neutralizing activity than the original vaccine based on the ancestral strain, although cross-neutralization responses against BA.4/BA.5 subvariants did not substantially increase. 30 We are not aware of previous studies that have assessed the immunogenicity elicited by the BA.4/BA.5-adapted bivalent booster dose in the SOT setting.…”
Section: Discussionmentioning
confidence: 99%